2000
DOI: 10.1111/j.1572-0241.2000.02090.x
|View full text |Cite
|
Sign up to set email alerts
|

alpha-1 antitrypsin deficiency and splenic artery aneurysm rupture: an association?

Abstract: The presence and risk of rupture of splenic artery aneurysms may be greater in patients with alpha-1 antitrypsin deficiency. If identified before rupture, an aggressive approach to diagnosing and treating these aneurysms should be initiated. At present, no consensus exists regarding the management of splenic artery aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Arterial aneurysms and spontaneous dissections have been found in various vascular districts [2,3], but to the best of our knowledge coronary ectatic vasculopathy has not been described in AAT deficiency previously. The affection of vessels might be explained by the degradation of elastic vascular fibres by enhanced activity of neutrophil elastase which can disrupt the integrity of the vessel wall and cause the formation of ectasia and/or aneurysm.…”
Section: Discussionmentioning
confidence: 77%
“…Arterial aneurysms and spontaneous dissections have been found in various vascular districts [2,3], but to the best of our knowledge coronary ectatic vasculopathy has not been described in AAT deficiency previously. The affection of vessels might be explained by the degradation of elastic vascular fibres by enhanced activity of neutrophil elastase which can disrupt the integrity of the vessel wall and cause the formation of ectasia and/or aneurysm.…”
Section: Discussionmentioning
confidence: 77%
“…In this study, up-regulation and inhibition of serpin B9 and serpinA3n (also called alpha 1-antitrypsin) were detected, respectively. It has been reported that patients with serpinA3n deficiency may be vulnerable to the development of splenic artery aneurysms [37], whereas overexpression of serpin B9 may prevent cytotoxic T-lymphocytes from eliminating certain tumor cells [38]. The different expression pattern of serpin B9 and serpinA3n can be markers of MCLR-induced damage in the spleen tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty per cent of cases are multiple and the commonest site is in the distal third of the splenic artery. Rupture of SAAs is rare, occurring in between 3 and 10% of cases (6, 7), but reported mortality from ruptured SAAs is between 25–65% (3, 8). The prevalence of SAAs in the general population is unknown but post‐mortem studies suggest that SAAs occur in 0.1–10% of healthy individuals, the incidence increasing with age (1, 2).…”
Section: Discussionmentioning
confidence: 99%
“…However, in adults with portal hypertension and chronic liver disease, the incidence may be as high as 50% as a result of increased splenic artery blood flow (3–5). Of these, 3–10% may rupture with a mortality of 25–65% (3, 6–8). The incidence of SAAs in children undergoing selective hepatic angiography prior to liver transplantation is reported as 4% (2), but there are few systematic studies.…”
mentioning
confidence: 99%